2021
DOI: 10.1177/03635465211029659
|View full text |Cite
|
Sign up to set email alerts
|

Relative Efficacy of Intra-articular Injections in the Treatment of Knee Osteoarthritis: A Systematic Review and Network Meta-analysis

Abstract: Background: In younger patients and those without severe degenerative changes, the efficacy of intra-articular (IA) injections as a nonoperative modality for treating symptomatic knee osteoarthritis (OA)–related pain while maintaining function has become a subject of increasing interest. Purpose: To assess and compare the efficacy of different IA injections used for the treatment of knee OA, including hyaluronic acid (HA), corticosteroids (CS), platelet-rich plasma (PRP), and plasma rich in growth factors (PRG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(26 citation statements)
references
References 62 publications
(67 reference statements)
0
20
0
Order By: Relevance
“…We focused on PRP (without leukocytes)(without stressing differences between formulations), as it is the most common formulation used in clinics [16], and current meta-analyses results refer to these PRP variants [20,21]. In parallel, we performed the same analyses for our in-house plasma preparations and found some differences in cluster analyses but similar results in terms of represented pathways.…”
Section: Discussionmentioning
confidence: 99%
“…We focused on PRP (without leukocytes)(without stressing differences between formulations), as it is the most common formulation used in clinics [16], and current meta-analyses results refer to these PRP variants [20,21]. In parallel, we performed the same analyses for our in-house plasma preparations and found some differences in cluster analyses but similar results in terms of represented pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Singh et al . 28 conducted a systematic review and network meta-analysis that demonstrated that all injectable agents (HA, PRP, and plasma rich in growth factors, except CSs resulted in statistically significant improvements in outcomes compared to placebo. Due to the large effect size, PRP showed clinically meaningful differences in functional improvement compared with CS and placebo.…”
Section: Discussionmentioning
confidence: 99%
“…concluded that the difference between PRP groups and HA groups in the clinical improvements of KOA was not significant. There have been numerous systematic reviews and meta-analyses, synthesizing preliminary studies and evaluating improvements in knee pain and function, generally confirming that PRP is beneficial for pain relief, and functional improvement, compared with HA and corticosteroids [ 41 , 42 ].…”
Section: Discussionmentioning
confidence: 99%